2015
DOI: 10.1177/2329490615604749
|View full text |Cite
|
Sign up to set email alerts
|

“You Don’t Have to Like Me, But You Have to Respect Me”

Abstract: This study investigates cooperativeness, assertiveness, group satisfaction, leader grade, and leadership negotiation in a collaborative assignment conducted in a small group. Researchers manipulated the assignment of team members who reported on measures of group satisfaction and original scales of assertiveness and cooperativeness. Respondents also responded to open-ended questions regarding active leadership, leadership traits, and leadership negotiation, which resulted in the emergence of multiple themes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The high impact of self-evaluation on assertiveness seems to be of great importance, meaning that the more positive self-evaluation, the higher the scores of assertiveness. Accordingly, establishing positive evaluation of self might lead to establishing assertive behavior (Alberti & Emmons, 2001;Ebru, 2011;Lambertz-Berndt & Blight, 2016;Paterson et al, 2002), possibly established through higher self-confidence that helps an individual to respond more assertively in interacting with others. In contrast, individuals with negative selfevaluation are entrapped with negative thoughts and feelings toward themselves that may lead to a non-assertive disposition (Parto, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high impact of self-evaluation on assertiveness seems to be of great importance, meaning that the more positive self-evaluation, the higher the scores of assertiveness. Accordingly, establishing positive evaluation of self might lead to establishing assertive behavior (Alberti & Emmons, 2001;Ebru, 2011;Lambertz-Berndt & Blight, 2016;Paterson et al, 2002), possibly established through higher self-confidence that helps an individual to respond more assertively in interacting with others. In contrast, individuals with negative selfevaluation are entrapped with negative thoughts and feelings toward themselves that may lead to a non-assertive disposition (Parto, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based results show that assertiveness skills vary in terms of age and gender, and they can clearly be improved (Hargie et al, 1994;Gripton & Valentich, 1993;Lambertz-Berndt & Blight, 2016). Assertiveness is thought to increase with age (Bu zan ci c, 2001; Cohen & Edwards, 1989;Maranguni c, 2002;Ryan et al, 2006) and may be maximized by biological and social maturation with possible gender differences (Zarevski & Mamula, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, assertiveness is described by most of the researchers. According to these descriptions, the assertive person can be aware of and maintain their rights, can admire others' rights (Jakubowski-Spector, 1973), can signify his positive and negative ideas and feelings fairly (Lambertz & Blight, 2016;De La Torre et al, 2021) can say "no" common time and states can do eye contact while speaking and communicating, can hold head and shoulders high while walking, can attend communicating with common hand and body movements, can use gestures and mimics appropriately, can use tone of voice suitably, can direct others, is open to criticize and being criticized (Lindenfield, 1997;Alberti & Emmons, 1998;Whirter & Acar, 2000;Goldin-Meadow & Alibali, 2013;Hall, Terrence & Murphy, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of assertiveness training is to help individuals change their attitudes towards themselves first and then to express their thoughts and feelings easily with self-confidence (Niusha et al, 2012;Lin et al, 2004;Obliagel, 2015). Research has shown that assertiveness training enhances positive human relations, affects personality behavior positively, and increases positive personal reactions in people who join assertiveness training (Lambertz & Blight, 2016;Lee et al, 2013). The basic item of these training programs is volunteering, and it is important to have high motivation (Kessler et al, 1986;Aydın, 1991;Deniz, 1997).…”
Section: Introductionmentioning
confidence: 99%